Overview of Climate Change Litigation. (2019) - Gerrard, Michael
Abstract : Climate change litigation is a global phenomenon. According to a database maintained by the Sabin Center for Climate Change Law, as of February 4, 2019 a total of 1, 297 climate cases had been filed in courts or other tribunals worldwide. Of these, 1, 009—78 percent—were from the United States, Australia was a distant second, with ninety-eight, followed by the United Kingdom with forty-seven. No other country had as many as twenty. The cases were filed in twenty-nine countries and six international tribunals, led by the Court of Justice of the European Union, which had forty-one.